Multilayered : Engineered Variety - Schlaich Bergermann Partner (Birkhäuser, 2019)
The firm schlaich bergermann partner has been designing and building ambitious civil engineering projects around the world for more than thirty years. Its portfolio ranges from long-span support structures and bridges to high-rises, special-use buildings and leading-edge solar power stations. The wellspring of the firm's innovative work lies in its unique planning culture. Beneath the Surface showcases this culture through sketches, drawings, photographs and texts from a wide selection of projects realized by schlaich bergermann partner. This impressive, richly illustrated volume brings into relief the firm's philosophy and the methods of its interdisciplinary engineers as they work together on equal footing with architects.